An environment monitoring system for a rice production model adaptive to climate change in the Mekong Delta of Viet Nam - Minh Thai Truong; Dai Nghia Nguyen; Minh Qui Trinh; Khoi Nghia Nguyen; Huu Thien Nguyen; Quy Khang Huynh; Ca Luu; Huynh Tram Vo (CTU Journal of Innovation and Sustainable Development)
This article presents an environment monitoring model for agricultural production applied to farmers in the Mekong Delta, Viet Nam. The proposed model's special feature is a system combining techniques such as IoT, agent-based, sensor networks, and data warehouses. Successfully deploying the model in monitoring the water level, and the environmental factors of the rice soil such as NPK, pH, EC, temperature, and soil moisture not only aids managers and farmers monitor environmental quality indicators in real time, but also experts to analyze data, give warnings and appropriate response solutions in agricultural production according to the pivot strategy towards Agriculture 4.0 proposed by the Minister of the Ministry of Agriculture and Rural Development of Viet Nam.